Association between the molecular markers, effect and time of response to the androgen-deprivation therapy in patients with prostate cancer - L. V. Spirina; A. K. Gorbunov; I. V. Kondakova; E. A. Usynin; E. M. Slonimskaya (Успехи молекулярной онкологии, 2019)
The expected effect of androgen-deprivation therapy is one of the important criteria when choosing therapy in patients with prostate cancer. No less significant factor is the time of its implementation. The study showed that high expression of androgen receptors (AR) in the tumor tissue against the background of low estrogen receptor α (ERα) expression is characteristic of patients in whom the effect of androgen-deprivation therapy was observed for 12 months. A set of parameters has been identified that makes it possible to predict the duration of response to androgen-deprivation therapy in patients with prostate cancer, which include the patient’s age, testosterone level, prostate specific antigen, expression level of AR, ERα. These data allow us to consider these parameters as additional informative markers, to predict not only the expected effect, but also its duration.